The Clash of Culture in Neil Gaiman's American Gods - Naya Fauzia Dzikrina; Achmad Munjid (Lexicon, 2018)
This research aims to examine the portrayal of cultural clash in Neil Gaiman’s novel, American Gods. More specifically, this research aims to identify what cultures are clashing and why they clash, and also to understand how the situation of cultural clash affects the lives and attitudes of the characters. This research also explores how the novel relates to cases of cultural clash happening in the current American society. This research is conducted using the framework of several sociological theories to understand the different forms of effects of cultural clash. The main issue presented in the novel is the conflict between the old gods, who represent society’s traditional beliefs, and the new gods, who represent the shift of culture in modern America. This conflict symbolizes how the two ideals, tradition and modernity, are competing in the American society today. The challenges the old gods face can also be seen as a portrayal of the immigrant experience, where they experience effects of cultural clash also commonly experienced by immigrants: cultural displacement, identity crisis, and conflict. The main finding of this research is that a person or group who experiences cultural clash will face a struggle where they must compromise or negotiate their cultural identity in order to be part of their current community. This is done as a way to survive and thrive in their environment.